GEOTOURISM VALORISATION OF SELECTED QUARRIES OF KŁODZKO REGION AND CIESZYN FOOTHILLS - Kasprowska-Nowak, Katarzyna; Marek, Aneta (Quaestiones Geographicae, 2019)
The article presents a geotourism valorisation of selected quarries located in different mountainous regions in southern Poland, diverse in geological and tectonic terms. The regions of Kłodzko (with quarries Kletno I, Krzyżnik, Sinica, Czarne Urwisko, Szczytna Zamek) and of Cieszyn Foothills (quarries Na Jasieniowej, Na Mołczynie, Grota na Rudowie, Nad Kalembianką, Ondraszkowa Dziura) were proposed as a case study. The survey describes the most exposed disused quarries of marble, gneiss, sandstone, teschenites and Cieszyn limestone of high natural and cultural significance. As a result of the geotourist valorisation, the analysed geological objects were given point score under various criteria (educational value, scientific value, visual value, location/accessibility value, cultural value, geo-infrastructural value and the value of legal protection). It was found that the discussed quarries reveal high natural and educational value, and they are very significant in education and promotion of geologically attractive areas.